Fix enhancement of road condition in Perlis using GIS approach / Nur Zakirah Rabiha Md Rejab - Md Rejab, Nur Zakirah Rabiha (2018)
The road is important public facility and transportation networks. Because of road condition, the accidents number are increased rapidly year by year. Previously, user will complain the road condition by Short Message Service (SMS) or calling Jabatan Kerja Raya (JKR) or any agencies. The action to respond will take a long time to process the complaints by the user. Thus, in this study, the real time complaint will be replacing traditional method which is by using Mobile Data Collection Apps. The objective of this study is to relate that land cover type that effeet road condition by using Geographic Information System (GIS) approach. As we know GIS is a system that helps to keep data storage and analysis. By GIS, road damage level can be classified and clustenzed by using GIS. For data collection. Mobile Data Collection Apps is used. This Apps is freely downloaded in Play store and Apps store. Once data was taken in real time by using a smartphone, it will be saved in Cloud GIS. Besides, satellite image Spot 6 is used to performed image-supervised classification. The results will be shown by several map layout that contains road damage. By refer to these results, it will achieve all the objective that state earlier. In conclusion, it can help the department or any agencies to realize that the road condition in Perlis is in good level or need road maintenance. Thus, this study can support the Road Safety Department of Malaysia in achieving the objective which is to reduce the number of accidents related to road damage factor.